Cross-cultural adaptation of the Malay version of the parent-proxy Health-Related Quality of Life Measure for Children with Epilepsy (CHEQOL-25) in Malaysia - Wo, S.W.; Lai, P.S.M.; Ong, L.C.; Low, W.Y.; Lim, K.S.; Tay, C.G.; Wong, C.P.; Ranjini, S. (Elsevier, 2015)
Purpose: We aimed to cross-culturally adapt the parent-proxy Health-Related Quality of Life Measure for Children with Epilepsy (CHEQOL-25) into Malay and to determine its validity and reliability among parents of children with epilepsy in Malaysia. Methods: The English version of the parent-proxy CHEQOL-25 was translated according to international guidelines to Malay. Content validity was verified by an expert panel and piloted in five parents of children with epilepsy (CWE). The Malay parent-proxy CHEQOL-25 was then administered to 40 parents of CWE, aged 8-18. years from two tertiary hospitals, at baseline and 2. weeks later. Parents were also required to complete the Malay PedsQL™ 4.0 so that convergent validity could be assessed. Hypothesis testing was assessed by correlating the individual subscales in the parent-proxy CHEQOL-25 with epilepsy severity, the number of anticonvulsants, and the number of close friends. Results: Participants from the pilot study did not encounter any problems in answering the final translated Malay parent-proxy CHEQOL-25. Hence, no further modifications were made. Cronbach's α for each subscale of the Malay parent-proxy CHEQOL-25 ranged from 0.67 to 0.83. The intraclass correlation coefficient for all items at test-retest ranged from 0.70 to 0.94. Both the CHEQOL-25 and the PedsQL™ 4.0 showed good correlation in the social and emotional subscales (r. =. 0.598, p. =. 0.002 and r. =. 0.342, p. =. 0.031, respectively). The severity of epilepsy, higher number of antiepileptic drug(s), poorer cognitive ability of the child, lower number of close friends, and lesser amount of time spent with friends were significantly associated with poorer health-related quality of life. Conclusions: The Malay parent-proxy CHEQOL-25 was found to be a valid and reliable instrument to assess parents' perceived HRQOL of their CWE in Malaysia.